Farmakološko zdravljenje centralne bolečine po možganski kapi - Perko, Denis (Zdravniški vestnik, 2009)
Background Central post-stroke pain belongs to the group of central neuropathic pain that may occur in patients after stroke. Most of the guidelines are based on rare randomised, placebo controlled studies and mostlyon uncontrolled studies, clinical experience, opinions of various experts and in comparison with the guidelines for the treatment of neuropathicpain in general. For clinical practice are important evidences on the effectiveness of drugs that show which drug is the most effective and which has at least side-effects. Methods We searched studies on the pharmacological treatment of central post-stroke pain on the basis of various search strategies in different databases. We focused on the search engine databases PubMed, where we looked at different combinations of results. The grade of evidence was defined in the following order: A - randomized, placebo-controlled studies, B - uncontrolled studies, C - clinical series or clinical reports. Results Amitriptyline, lamotrigrine and pregabalin are oral drugs that have proved to be effectivein the treatment of central post-stroke pain in placebo-controlled studies (p < 0.05; grade of evidence A). Gabapentinand mexiletine showed effectiveness in uncontrolled studies (p < 0,05; grade of evidence B). Parentheral drugs, such as lidocaine, propofol andketamine, have shown good performance in the short-term pain control in randomized, placebocontrolled studies (p < 0.05; grade of evidence). Conclusions Amitriptyline, lamotrigine, gabapentin and pregabalin provide better performance and safety than traditional neuromodulators as carbamazepine and phenytoin. Randomized controlled clinical studies are rare and they have included only a small number of patients.
Keywords: Anticonvulsants; Antidepresivi; Antidepressive Agents; Antikonvulzivi; Bolečina; Cerebral Infarction; drug; Drug Therapy; možganska kap; Možganski infarkt; Narcotics; Narkotiki; Neuralgia; Nevralgija; Pain; therapy; zdravila; zdravljenje